KEANEKARAGAMAN DAN PENYEBARAN GALL DI KEBUN RAYA BOGOR - Rachman, Erlin; Tihurua, Eka Fatmawati; Sunaryo, Sunaryo (Buletin Kebun Raya, 2012)
In order to know the habitat preference gradation for gall-forming insects from the border to the middle of the habitat or more precise the edge effect on the galling existence and the expansion ability of local gall to infect on non indigenous species, observation of all plant life collections block by block in the Bogor Botanic Garden were done. Host plant and galling insect species composition differed quite characteristically between the edge and the interior of paths, but did not for galling insect richness. Insect gall richness was expressed as the ratio between insect gall and host plant richness (gall per plant ratio) and in the same time a weak relationship of insect speciesâarea was found. Our results suggest that the number of galling insects per individual plant is not affected by the size of the patch. Despite these results, the natural forest patches are found in this region seem well suited for long-term studies addressing speciesâarea relationships.